GC–MS analysis of bioactive compounds present in different extracts of rhizome of Curcuma aeruginosa Roxb. - VJ, Dessy; Sivakumar, S.R.; George, Mariat; francis, Steffy (Journal of Drug Delivery and Therapeutics, 2019)
To analyze and characterize the chemical composition of the different crude extracts from the rhizome of Curcuma aeruginosa Roxb a medicinal plant.The air-dried rhizomes were powdered and subjected to Soxhlet extraction using solvent n-hexane and Supercritical fluid extraction. Then, each of the extracts was further subjected to gas chromatography-mass spectrometry. Qualitative determination of the different biologically active compounds from crude extracts of C aeruginosa Roxb using gas chromatography–mass spectrometry revealed different types of high and low molecular weight chemical entities with varying quantities present in each of the extracts. These chemical compounds are considered biologically and pharmacologically important. Furthermore, the two different extracts SCF and n-hexane possess unique physicochemical characteristics. The two extracts possess major bioactive compounds that were identified and characterized spectroscopically. Thus, identification of different biologically active compounds in the extracts of C aeruginosa Roxb warrants further biological and pharmacological studies.Keywords: Supercritical Fluid, Soxhlet extraction, GC-MS